The Role of Autophagy in Gastric Cancer Chemoresistance: Friend or Foe? - Xu, Jing-Li; Yuan, Li; Tang, Yan-Cheng; Xu, Zhi-Yuan; Xu, Han-Dong; Cheng, Xiang-Dong; Qin, Jiang-Jiang (Frontiers in Cell and Developmental Biology, 2020)
Gastric cancer is the third most common cause of cancer-related death worldwide. Drug resistance is the main inevitable and vital factor leading to a low 5-year survival rate for patients with gastric cancer. Autophagy, as a highly conserved homeostatic pathway, is mainly regulated by different proteins and non-coding RNAs (ncRNAs) and plays dual roles in drug resistance of gastric cancer. Thus, targeting key regulatory nodes in the process of autophagy by small molecule inhibitors or activators has become one of the most promising strategies for the treatment of gastric cancer in recent years. In this review, we provide a systematic summary focusing on the relationship between autophagy and chemotherapy resistance in gastric cancer. We comprehensively discuss the roles and molecular mechanisms of multiple proteins and the emerging ncRNAs including miRNAs and lncRNAs in the regulation of autophagy pathways and gastric cancer chemoresistance. We also summarize the regulatory effects of autophagy inhibitor and activators on gastric cancer chemoresistance. Understanding the vital roles of autophagy in gastric cancer chemoresistance will provide novel opportunities to develop promising therapeutic strategies for gastric cancer.